THE SUCCESSFUL APPLICATION OF AUGMENTED REALITY AND ITS IMPACT ON SELF-PRESENCE: AUGMENTED REALITY USAGE IN SNAPCHAT AND ITS IMPACT ON CONSUMERS (Proceedings of the World Conference on Media and Mass Communication, 2023)
Despite their potential as interactive marketing tools, Augmented reality (AR) filters are frequently used as a social media feature that provides users with various visual effects. This study explores the audience's emotional responses to augmented reality (AR) while using Snapchat filters as a self-presence tool. It focuses on the user's interactions with Snapchat Face Lenses, especially how they choose one and behave when using it. The study adopted a quantitative method design to collect quantitative data from different Snapchat users by using a closed-ended survey instrument. The quantitative data was analysed descriptively using the mean and the standard deviation. The results revealed that depending on the underlying cause of AR filter usage, these uses might have both positive and negative consequences regards to curiosity and compatibility with users' contentment. Therefore, Specialists should include the necessary elements while creating the filters to give consumers enjoyable and exciting experiences, the chance to socialise, and access to new material. Finally, The study suggests further research to examine augmented reality filters on other social media sites to indicate whether the outcomes vary depending on the platform.
Keywords: Snapchat; Social Media; Augmented Reality; AR Filters